Evaluation of Parents’ Knowledge about Nutritional Management of Children with Phenylketonuria - Salih, Mustafa; Mohammed, Qahtan Q. (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): to evaluate parents’ knowledge about nutritional management of children with phenylketonuria and to find out the differences between parents’ knowledge about nutritional management and their demographic variables of parents such as (parental age and socioeconomic status). Methodology: A non-experimental design; was conducted on parents of phenylketonuria child, from the period 3 June to 5 October 2022. A Non-probability sample of 35 PKU children and their parents were selected conveniently from the hospitals that are select for the study. A questionnaire is constructed for the purpose of the study. It composed of two parts: The validity analysis shows very good evaluation for knowledge scale. Data are analyzed using Statistical Data Analysis by using SPSS. Results: Results showed that (62.9%) of the parents showing moderate knowledge of Parents about and nutrition knowledge of children with phenylketonuria. Conclusions: Overall evaluation of Parents’ knowledge showing moderate knowledge about nutritional management and the study confirms that older parents are better knowledge. Recommendations: The study recommends that parents of phenylketonuria children should be very well-oriented and greatly aware about the importance of nutritional management, and also offers an educational program for parents’ of children with PKU.